Explosion-proof membrane and preparation method thereof
By using specific combinations of adhesive layer materials and preparation techniques in the explosion-proof film, the problems of low peeling force and degumming in high temperature and high humidity environments are solved, and its initial viscosity and weather resistance are improved.
Patent Information
- Application Number
- CN202211075201.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-04
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-09-04
AI Technical Summary
The peeling force of the existing explosion-proof film is significantly reduced when used in high-temperature and high-humidity environments for a long time, and it is easy to cause degumming.
Adhesive layer including PET base film, release film and bonding PET base film and release film. The adhesive layer consists of acrylate copolymer, tackifying resin, coupling agent, curing agent and catalyst, and is electrically charged. Prepared by halo treatment and rubber roller bonding technology, the adhesive layer thickness is between 20-50μm and the curing temperature is between 100℃ and 150℃.
The initial viscosity and peeling force of the explosion-proof film are improved, and its weather resistance in high temperature and high humidity environments are enhanced, which effectively solves the problems of low peeling force and degumming.
Smart Images

Figure GHA0000008714810000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of protective films and relates to an explosion-proof film and a preparation method thereof. Background Art
[0002] The explosion-proof film has a wide range of uses. Its main structure is to coat a high-performance and high-adhesive adhesive layer on an optical-grade PET substrate. It is suitable for protecting the outer layer of display screens or back cover glass materials such as mobile phones and tablets. It prevents the outer layer of the display screen or back cover glass from being broken by external forces, which poses a safety hazard to users. At present, the explosion-proof film has high initial adhesion and low peeling force. Especially when used for a long time in a high temperature and high humidity environment, the peeling force is significantly reduced, and debonding is prone to occur in a high temperature and high humidity environment. Summary of the invention
[0003] The object of the present invention is to provide an explosion-proof film and a preparation method thereof, which can effectively solve the problem of low peeling force of the explosion-proof film, especially the obvious reduction of peeling force and degumming when used for a long time in a high temperature and high humidity environment.
[0004] To achieve the above object, the present invention proposes the following technical solution: an explosion-proof film, comprising a PET base film, a release film, and an adhesive layer for bonding the PET base film and the release film, wherein the adhesive layer is formed by curing an adhesive, and the adhesive comprises the following substances in parts by weight:
[0005] Acrylate copolymer: 50-70 parts
[0006] Solvent: 20-45 parts
[0007] Tackifying resin: 2.5-4 parts
[0008] Coupling agent: 0.5-2 parts
[0009] Curing agent: 1.5-3 parts
[0010] Catalyst: 0.5-1 part
[0011] The molecular weight of the acrylic copolymer is between 1 million and 2 million;
[0012] The tackifying resin is one of dicyclopentadiene resin, alkylphenol-formaldehyde resin, or xylene resin;
[0013] The solvent is one of an ester-containing organic solvent and a ketone-containing organic solvent, or two of them in any weight ratio; wherein the ester-containing organic solvent is one of ethyl acetate and butyl acetate, or a combination of multiples in any weight ratio; the ketone-containing organic solvent is one of cyclohexanone, butanone, and methyl isobutyl ketone, or a combination of multiples in any weight ratio;
[0014] The coupling agent is a silane coupling agent;
[0015] The curing agent includes an epoxy curing agent and an isocyanate curing agent, and the usage ratio of the two is 1:(2-5);
[0016] The catalyst is any one of dibutyltin dilaurate, dioctyltin dilaurate, and dibutyltin acetate;
[0017] The method for preparing the explosion-proof membrane comprises the following steps:
[0018] 1. Preparation of adhesive layer coating liquid:
[0019] Dissolving a proportion of an acrylic copolymer in a solvent, adding a tackifying resin, and stirring to obtain an acrylic copolymer solution;
[0020] Adding a coupling agent, a curing agent and a catalyst in a proportioned amount to the acrylic copolymer solution prepared above in sequence, and stirring to obtain an adhesive layer coating solution;
[0021] 2. Coating adhesive layer coating liquid:
[0022] Apply the adhesive layer coating liquid to the corona-treated side of the PET base film and cure it at 100°C-150°C to form an adhesive layer;
[0023] 3. Forming explosion-proof film:
[0024] The release surface of the PET release film and the adhesive layer are laminated by a rubber roller to obtain an explosion-proof film.
[0025] As a preferred technical solution of the present application, the adhesive layer is between 20-50 μm.
[0026] As a preferred technical solution of the present application, the curing temperature of the adhesive to form an adhesive layer is between 100°C and 150°C.
[0027] As a preferred technical solution of the present application, the side of the PET base film used for coating the adhesive layer is subjected to corona treatment.
[0028] As a preferred technical solution of the present application, the thickness of the PET base film is 25-380 μm.
[0029] As a preferred technical solution of the present application, the release force of the release film is 15-100g, and the release film is a PET release film.
[0030] As a preferred technical solution of the present application, the release surface of the PET release film is bonded to the adhesive layer by means of a rubber roller.
[0031] Beneficial effects:
[0032] 1. Tackifying resins basically contain phenolic hydroxyl, methylol, carboxyl, ester bond, ether bond, etc., which can easily form a hydrogen bond network structure with the resin to obtain the best viscosity. Adding tackifying resin to acrylate copolymers as a modifier of acrylate copolymers can increase the viscosity of acrylate copolymer solutions, improve initial viscosity, and at the same time improve peeling force and weather resistance.
[0033] 2. Coupling agents are generally composed of two parts: one part is an inorganic-friendly group that can react with inorganic fillers or reinforcing materials; the other part is an organic-friendly group that can react with resins. Adding coupling agents to the adhesive layer coating liquid increases the affinity of acrylic copolymers, organic solvents and tackifying resins to improve the dispersibility of the above substances in organic solvents, improve the adhesion between the adhesive layer and the PET film, solve the problem of degumming, and increase the weather resistance of the explosion-proof film.
[0034] 3. Since the thickness of the explosion-proof film adhesive layer is between 20-50μm, it is necessary to quickly cross-link and cure on the coating line. Adding a catalyst to the adhesive layer coating liquid can shorten the cross-linking and curing reaction time and prevent the adhesive layer from not reacting completely.
[0035] 4. The adhesive layer coating liquid of the present invention increases the viscosity of the coating liquid and the dispersibility of the acrylic copolymer in the organic solvent by adding a tackifying resin and a coupling agent. The adhesive layer formed after coating can improve the initial adhesion, peeling force, adhesion between the adhesive layer and the PET film, and weather resistance of the explosion-proof film.
[0036] In summary, the technical solution of the present application can effectively solve the problem of low peeling force of the explosion-proof film, especially the obvious reduction of peeling force and degumming after long-term use in high temperature and high humidity environment, thereby ensuring the performance of the explosion-proof film.
[0037] It should be appreciated that all combinations of the foregoing concepts, as well as additional concepts described in greater detail below, may be considered to be part of the inventive subject matter of the present disclosure, provided such concepts are not mutually inconsistent. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be understood by people with ordinary skills in the field to which the present invention belongs.
[0039] An explosion-proof film includes a PET base film, a release film, and an adhesive layer for bonding the PET base film and the release film, wherein the adhesive layer is formed by curing an adhesive, and the adhesive includes the following substances in parts by weight:
[0040] Acrylate copolymer: 50-70 parts
[0041] Solvent: 20-45 parts
[0042] Tackifying resin: 2.5-4 parts
[0043] Coupling agent: 0.5-2 parts
[0044] Curing agent: 1.5-3 parts
[0045] Catalyst: 0.5 part to 1 part.
[0046] The molecular weight of the acrylic ester copolymer is between 1 million and 2 million.
[0047] The solvent is one of an ester-containing organic solvent and a ketone-containing organic solvent or two of them in any weight ratio; wherein the ester-containing organic solvent is one of ethyl acetate and butyl acetate or a combination of multiples in any weight ratio; the ketone-containing organic solvent is one of cyclohexanone, butanone, and methyl isobutyl ketone or a combination of multiples in any weight ratio. The use of the above-mentioned organic solvent with higher polarity can effectively inhibit the generation of gel points in the adhesive layer coating liquid, and can effectively control the coating lines generated by gel points during coating.
[0048] The tackifying resin is one of dicyclopentadiene (DCPD) resin, alkylphenolic resin, or xylene resin. As a modifier of the acrylic copolymer, the viscosity of the acrylic copolymer solution is increased, the initial adhesion is increased, and the peeling force and weather resistance are increased.
[0049] The coupling agent is a silane coupling agent, preferably any one of KH550, KH560, KH570, KH792, and DL602, which increases the affinity of the acrylic copolymer, the organic solvent, and the tackifying resin to improve the dispersibility of the above substances in the organic solvent, improve the adhesion between the adhesive layer and the PET film, solve the problem of degumming, and increase the weather resistance of the explosion-proof film.
[0050] The curing agent includes an epoxy curing agent and an isocyanate curing agent, and the usage ratio of the two is 1: (2-5). The epoxy curing agent is preferably any one of LITE3000, LITE3005, LITE3100, LITE3117, LITE2562, and GX5618. The isocyanate curing agent is preferably any one of WANNATE HT-100, WANNATE PM-130, WANNATE TDI-80, WANNATEHT-90, WANNATE PM-200, and WANNATE HEMA-98. The curing agent reacts with the acrylic copolymer to form a crosslinking agent, so that multiple linear molecules are bonded and crosslinked to form a network structure.
[0051] The catalyst is any one of dibutyltin dilaurate, dioctyltin dilaurate, and dibutyltin acetate. Adding the catalyst to the adhesive layer coating liquid can shorten the crosslinking and curing reaction time and prevent the adhesive layer from not reacting completely. The amount of the catalyst used in this application is to ensure that the crosslinking and curing reaction time is between 30s and 120s, which can achieve the effect of complete crosslinking and curing.
[0052] The thickness of the adhesive layer is between 20 and 50 μm. The thickness of the adhesive layer is limited in the present invention to prevent the adhesive layer from being too thick and affecting the curing effect, and from being too thin and affecting the peeling force of the adhesive layer.
[0053] The curing temperature of the adhesive to form the adhesive layer is between 100° C. and 150° C. The curing temperature is limited in the present invention to prevent the adhesive layer from overflowing due to inappropriate curing temperature and incomplete cross-linking reaction.
[0054] Another object of the present application is to provide an explosion-proof film, comprising a PET base film, a release film, and an adhesive layer for bonding the PET base film and the release film. Preferably, the thickness of the PET base film is 25-380 μm. The present invention limits the thickness of the PET base film to prevent the PET base film from being too thin, resulting in the base film being unable to support the adhesive layer. Preferably, the release force of the release film is 15-100g of the PET release film. The present invention limits the release force of the release film to prevent the release force from being too large, resulting in the release surface and the adhesive layer being too closely attached and difficult to tear apart.
[0055] As a preferred technical solution of the present application, the side of the PET base film used for coating the adhesive layer is subjected to corona treatment, and the purpose of the corona treatment is to enhance the adhesion between the adhesive layer and the PET base film.
[0056] As a preferred technical solution of the present application, the release surface of the PET release film is bonded to the adhesive layer by means of a rubber roller, which can effectively prevent the release surface of the release film and the adhesive layer from being compounded to form bubble points.
[0057] Another object of the present application is to provide a method for preparing an explosion-proof film, comprising the following steps:
[0058] 1. Preparation of adhesive layer coating liquid:
[0059] Dissolving a proportion of an acrylic copolymer in a solvent, adding a tackifying resin, and stirring to obtain an acrylic copolymer solution;
[0060] Adding a coupling agent, a curing agent and a catalyst in a proportioned amount to the acrylic copolymer solution prepared above in sequence, and stirring to obtain an adhesive layer coating solution;
[0061] 2. Coating adhesive layer coating liquid:
[0062] Apply the adhesive layer coating liquid to the corona-treated side of the PET base film and cure it at 100°C-150°C to form an adhesive layer;
[0063] 3. Forming explosion-proof film:
[0064] The release surface of the PET release film and the adhesive layer are laminated by a rubber roller to obtain an explosion-proof film.
[0065] The present invention will be further described below in conjunction with specific embodiments.
[0066] Example 1
[0067] S1. Dissolve 50 g of an acrylic copolymer in 45 g of ethyl acetate, add 2.5 g of dicyclopentadiene (DCPD) resin, and stir to obtain an acrylic copolymer solution.
[0068] S2. 0.5 g of KH550 was added to the above-prepared acrylic copolymer solution in sequence and stirred thoroughly, then 1.5 g of curing agent (LITE3000:WANNATE HT-100=1:2) was added, and finally 0.5 g of dibutyltin dilaurate was added, and the adhesive layer coating solution was obtained after stirring.
[0069] S3. Apply the adhesive layer coating liquid obtained in step S2 to the corona-treated side of the PET base film at 100° C. to form an adhesive layer. The thickness of the adhesive layer is 20 μm, and the thickness of the PET base film is 25 μm.
[0070] S4. Laminating the PET release film to the adhesive layer in step S3 by means of a rubber roller to obtain an explosion-proof film, wherein the release force of the release film is 15 g.
[0071] The performance test results are shown in Table 1.
[0072] Example 2
[0073] S1. Dissolve 55 g of acrylic copolymer in 39 g of butyl acetate, add 3 g of alkylphenol-formaldehyde resin, and stir evenly to obtain an acrylic copolymer solution.
[0074] S2. 1 g of KH560 was added to the above-prepared acrylic copolymer solution in sequence and stirred thoroughly, then 2 g of curing agent (LITE3005:WANNATE PM-130=1:3) was added, and finally 0.6 g of dioctyltin dilaurate was added, and the mixture was stirred to obtain an adhesive layer coating solution.
[0075] S3. Apply the adhesive layer coating liquid obtained in step S2 to the corona-treated side of the PET base film at 110° C. to form an adhesive layer. The thickness of the adhesive layer is 25 μm, and the thickness of the PET base film is 50 μm.
[0076] S4. Laminating the PET release film to the adhesive layer in step S3 by means of a rubber roller to obtain an explosion-proof film, wherein the release force of the release film is 25 g.
[0077] The performance test results are shown in Table 1.
[0078] Example 3
[0079] S1. Dissolve 60 g of acrylic copolymer in 34 g of cyclohexanone, add 3.2 g of xylene resin, and stir evenly to obtain an acrylic copolymer solution.
[0080] S2. 1.3 g of KH570 was added to the above-prepared acrylic copolymer solution in sequence and stirred thoroughly, then 2.4 g of curing agent (LITE3100:WANNATE TDI-80=1:3) was added, and finally 0.7 g of dibutyltin acetate was added and stirred to obtain an adhesive layer coating solution.
[0081] S3. Apply the adhesive layer coating liquid obtained in step S2 to the corona-treated side of the PET base film at 120° C. to form an adhesive layer. The thickness of the adhesive layer is 30 μm, and the thickness of the PET base film is 125 μm.
[0082] S4. Laminating the PET release film to the adhesive layer in step S3 by means of a rubber roller to obtain an explosion-proof film, wherein the release force of the release film is 50 g.
[0083] The performance test results are shown in Table 1.
[0084] Example 4
[0085] S1. Dissolve 65 g of acrylic copolymer in 29 g of butanone, add 3.5 g of dicyclopentadiene (DCPD) resin, and stir evenly to obtain an acrylic copolymer solution.
[0086] S2. 1.5 g of KH792 was added to the above-prepared acrylic copolymer solution in sequence and stirred thoroughly, then 2.6 g of curing agent (LITE3117:WANNATE HT-90=1:4) was added, and finally 0.8 g of divinyltetramethyldisiloxane platinum complex was added, and the adhesive layer coating solution was obtained after stirring.
[0087] S3. Apply the adhesive layer coating liquid obtained in step S2 to the corona-treated side of the PET base film at 130° C. to form an adhesive layer. The thickness of the adhesive layer is 35 μm, and the thickness of the PET base film is 188 μm.
[0088] S4. Laminating the PET release film to the adhesive layer in step S3 by means of a rubber roller to obtain an explosion-proof film, wherein the release force of the release film is 65 g.
[0089] The performance test results are shown in Table 1.
[0090] Example 5
[0091] S1. Dissolve 70 g of an acrylic copolymer in 20 g of methyl isobutyl ketone, add 4 g of dicyclopentadiene (DCPD) resin, and stir to obtain an acrylic copolymer solution.
[0092] S2. Add 2 g of DL602 to the above-prepared acrylic copolymer solution in sequence and stir thoroughly, then add 3 g of curing agent (LITE2562:WANNATE PM-200=1:5), and finally add 1 g of dibutyltin dilaurate, and stir to obtain an adhesive layer coating solution.
[0093] S3. Apply the adhesive layer coating liquid obtained in step S2 to the corona-treated side of the PET base film at 140° C. to form an adhesive layer. The thickness of the adhesive layer is 40 μm, and the thickness of the PET base film is 250 μm.
[0094] S4. Laminating the PET release film to the adhesive layer in step S3 by means of a rubber roller to obtain an explosion-proof film, wherein the release force of the release film is 85 g.
[0095] The performance test results are shown in Table 1.
[0096] Example 6
[0097] S1. Dissolve 68 g of an acrylic copolymer in a mixed solution of 24 g of ethyl acetate and methyl isobutyl ketone (ethyl acetate: methyl isobutyl ketone = 1:2), then add 3.7 g of dicyclopentadiene (DCPD) resin, and stir evenly to obtain an acrylic copolymer solution.
[0098] S2. 1.7 g DL602 was added to the above-prepared acrylic copolymer solution in sequence and stirred thoroughly, then 2.8 g curing agent (GX5618: WANNATE HEMA-98 = 1:5) was added, and finally 0.9 g dibutyltin dilaurate was added, and the mixture was stirred to obtain an adhesive layer coating solution.
[0099] S3. Apply the adhesive layer coating liquid obtained in step S2 to the corona-treated side of the PET base film at 150° C. to form an adhesive layer. The thickness of the adhesive layer is 50 μm, and the thickness of the PET base film is 380 μm.
[0100] S4. Laminating the PET release film to the adhesive layer in step S3 by means of a rubber roller to obtain an explosion-proof film, wherein the release force of the release film is 100 g.
[0101] The performance test results are shown in Table 1.
[0102] Comparative Example 1 of Example 1
[0103] S1. Dissolve 50 g of an acrylic acid ester copolymer in 45 g of ethyl acetate and stir evenly to obtain an acrylic acid ester copolymer solution.
[0104] S2. 0.5 g of KH550 was added to the above-prepared acrylic copolymer solution in sequence and stirred thoroughly, then 1.5 g of curing agent (LITE3000:WANNATE HT-100=1:2) was added, and finally 0.5 g of dibutyltin dilaurate was added, and the adhesive layer coating solution was obtained after stirring.
[0105] S3. Apply the adhesive layer coating liquid obtained in step S2 to the corona-treated side of the PET base film at 100° C. to form an adhesive layer. The thickness of the adhesive layer is 20 μm, and the thickness of the PET base film is 25 μm.
[0106] S4. Laminating the PET release film to the adhesive layer in step S3 by means of a rubber roller to obtain an explosion-proof film, wherein the release force of the release film is 15 g.
[0107] The performance test results are shown in Table 1.
[0108] Comparative Example 2 of Example 1
[0109] S1. Dissolve 50 g of the acrylic copolymer in 45 g of ethyl acetate, add 2.5 g of dicyclopentadiene (DCPD) resin, and stir evenly to obtain an acrylic copolymer solution.
[0110] S2. Add 1.5 g of curing agent (LITE3000:WANNATEHT-100=1:2) to the acrylic copolymer solution prepared above, and finally add 0.5 g of dibutyltin dilaurate, and stir to obtain an adhesive layer coating solution.
[0111] S3. Apply the adhesive layer coating liquid obtained in step S2 to the corona-treated side of the PET base film at 100° C. to form an adhesive layer. The thickness of the adhesive layer is 20 μm, and the thickness of the PET base film is 25 μm.
[0112] S4. Laminating the PET release film to the adhesive layer in step S3 by means of a rubber roller to obtain an explosion-proof film, wherein the release force of the release film is 15 g.
[0113] The performance test results are shown in Table 1.
[0114] Comparative Example 3 of Example 1
[0115] S1. Dissolve 50 g of an acrylic copolymer in 45 g of ethyl acetate, add 2.5 g of dicyclopentadiene (DCPD) resin, and stir to obtain an acrylic copolymer solution.
[0116] S2. 0.5 g of KH550 was added to the above-prepared acrylic copolymer solution in sequence and stirred thoroughly, and then 1.5 g of curing agent (LITE3000:WANNATE HT-100=1:2) was added and stirred to obtain an adhesive layer coating solution.
[0117] S3. Apply the adhesive layer coating liquid obtained in step S2 to the corona-treated side of the PET base film at 100° C. to form an adhesive layer. The thickness of the adhesive layer is 20 μm, and the thickness of the PET base film is 25 μm.
[0118] S4. Laminating the PET release film to the adhesive layer in step S3 by means of a rubber roller to obtain an explosion-proof film, wherein the release force of the release film is 15 g.
[0119] The performance test results are shown in Table 1.
[0120] The performance test methods in Table 1 are as follows:
[0121] The peeling force test of explosion-proof film refers to the standard GB / T2792-2004; the initial adhesion test of explosion-proof film refers to the standard GB / T31125-2004; the weather resistance test conditions are 60℃×90%RH×72h, and the explosion-proof film is cut into samples with a width of 25mm and a length of 200mm, and affixed to a steel plate for testing.
[0122] Table 1 Performance data of each embodiment
[0123]
[0124] It can be seen from the test data of the embodiments and comparative examples that the peeling force, initial adhesion and weather resistance of the explosion-proof film prepared by adopting the technical scheme of the present invention are greatly improved, which can effectively solve the problem of low peeling force of the existing explosion-proof film, especially the obvious reduction of peeling force and degumming when used for a long time in a high temperature and high humidity environment.
[0125] The above is only an embodiment of the present invention, and its description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. An explosion-proof film, comprising a PET base film, a release film, and an adhesive layer for bonding the PET base film and the release film, characterized in that: The adhesive layer is formed by curing an adhesive, and the adhesive includes the following substances in parts by weight: Acrylate copolymer: 50-70 parts Solvent: 20-45 parts Tackifying resin: 2.5-4 parts Coupling agent: 0.5-2 parts Curing agent: 1.5-3 parts Catalyst: 0.5-1 part The molecular weight of the acrylic copolymer is between 1 million and 2 million; The tackifying resin is one of dicyclopentadiene resin, alkylphenolic resin, or xylene resin; the curing agent includes epoxy curing agent and isocyanate curing agent, and the usage ratio of the two is 1: (2-5); The method for preparing the explosion-proof membrane comprises the following steps:
1. Preparation of adhesive layer coating liquid: Dissolving a proportion of an acrylic copolymer in a solvent, adding a tackifying resin, and stirring to obtain an acrylic copolymer solution; Adding a coupling agent, a curing agent and a catalyst in a proportioned amount to the acrylic copolymer solution prepared above in sequence, and stirring to obtain an adhesive layer coating solution; 2. Coating adhesive layer coating liquid: Apply the adhesive layer coating liquid to the corona-treated side of the PET base film and cure it at 100°C-150°C to form an adhesive layer; Forming explosion-proof membrane: The release surface of the PET release film and the adhesive layer are laminated by a rubber roller to obtain an explosion-proof film; The solvent is one of an ester-containing organic solvent and a ketone-containing organic solvent, or two of them in any weight ratio; wherein the ester-containing organic solvent is one of ethyl acetate and butyl acetate, or a combination of multiples in any weight ratio; the ketone-containing organic solvent is one of cyclohexanone, butanone, and methyl isobutyl ketone, or a combination of multiples in any weight ratio; The coupling agent is a silane coupling agent; The catalyst is any one of dibutyltin dilaurate, dioctyltin dilaurate and dibutyltin acetate.
2. The explosion-proof membrane according to claim 1, characterized in that: The thickness of the adhesive layer is between 20-50 μm.
3. The explosion-proof membrane according to claim 1, characterized in that: The curing temperature of the adhesive layer is between 100°C and 150°C.
4. The explosion-proof membrane according to claim 1, characterized in that: The side of the PET base film used for coating the adhesive layer is subjected to corona treatment.
5. The explosion-proof membrane according to claim 4, characterized in that: The thickness of the PET base film is 25-380 μm.
6. The explosion-proof membrane according to claim 1, characterized in that: The release film has a release force of 15-100 g and is a PET release film.
7. The explosion-proof membrane according to claim 6, characterized in that: The release surface of the PET release film is bonded to the adhesive layer by means of a rubber roller.
Citation Information
Patent Citations
Preparation method of adhesive-feeling-free heat-shrinkable heat-sticking universal high-transmittance protective film
CN112760065A
Cited By
Anti-aging explosion-proof membrane adhesive with low initial adhesion, high stripping force and preparation method of anti-aging explosion-proof membrane adhesive
CN121406264A